Characterization of the Complete Nucleotide Sequences of IncA/C2 Plasmids Carrying In809-Like Integrons from Enterobacteriaceae Isolates of Wildlife Origin - Papagiannitsis, Costas C; Kutilova, Iva; Medvecky, Matej; Hrabak, Jaroslav; Dolejska, Monika (Antimicrobial agents and chemotherapy, 2017)
A total of 18 Enterobacteriaceae (17 from gulls and 1 from a clinical sample) collected from Australia, carrying IncA/C plasmids with the IMP-encoding In809-like integrons, were studied. Seven plasmids, being representatives of different origins, plasmid sizes, replicon combinations, and resistance genes, were completely sequenced. Plasmid pEc158, identified in a clinical Escherichia coli ST752 isolate, showed extensive similarity to type 2 IncA/C2 plasmids. pEc158 carried none of the blaCMY-2-like region or ARI-B and ARI-A regions, while it contained a hybrid transposon structure. The six remaining plasmids, which were of wildlife origin, were highly similar to each other and probably were fusion derivatives of type 1 and type 2 A/C2 plasmids. The latter plasmids contained an ARI-B region and hybrid transposon structures. In all plasmids, hybrid transposon structures containing In809-like integrons were inserted 3,434 bp downstream of the rhs2 start codon. In all cases, the one outermost 38-bp inverted repeat (IR) of the transposon was associated with the Tn1696 tnp module, while the other outermost 38-bp IR of the transposon was associated with either a Tn6317-like module or a Tn21 mer module. However, the internal structure of the transposon and the resistance genes were different in each plasmid. These findings indicated that, for the specific periods of time and settings, different IncA/C2 plasmid types carrying In809-like elements circulated among isolates of wildlife and clinical origins. Additionally, they provided the basis for speculations regarding the reshuffling of IncA/C2 plasmids with In809-like integrons and confirmed the rapid evolution of IncA/C2 plasmid lineages.
Keywords: Anti-Bacterial Agents; mnohočetná bakteriální léková rezistence; transpozibilní elementy DNA; sekvence nukleotidů; Austrálie; Humans; lidé; Citrobacter freundii; Microbial Sensitivity Tests; sekvenční analýza DNA; Klebsiella pneumoniae; Sequence Analysis, DNA; zvířata; Animals; Plasmids; beta-Lactamases; plazmidy; beta-laktamasy; mikrobiální testy citlivosti; Australia; antibakteriální látky; Escherichia coli; Charadriiformes; Base Sequence; DNA Transposable Elements; Drug Resistance, Multiple, Bacterial; obrácené repetice; Inverted Repeat Sequences